DANANTARA (INVESTMENT MANAGEMENT INSTITUTION): AN INDONESIAN COMPETITIVE LAW PERSPECTIVE - Upita Anggunsuri; Shafira Hijriya (JCH (Jurnal Cendekia Hukum), 2026)
This study analyzes Danantara (Investment Management Institution): An Indonesian Competition Law Perspective. This research endeavors to answer the following questions: How is Danantara's independence from a governance perspective, and what challenges does Danantara face in creating inter-institutional and cross-sectoral relations from the perspective of business competition law in Indonesia? This study employs a normative juridical method, using statutory and conceptual approaches. The study concludes that Danantara has to implement GCG principles (Transparency, Accountability, Responsibility, Independence, Fairness) to manage State-Owned Enterprises (BUMN) and investments. However, the enactment of Law No. 16 of 2025, there are several articles may affect Danantara's independence and potentially give rise to abuse of power, namely Article 3F point g, which stipulates that Danantara, in the process of formulating the work plan and budget of the investment and operational holding company, must consult with the House of Representatives (DPR), and Article 4A point 3 show that the mechanism for capital participation in the context of establishing state-owned enterprises must obtain approval from the DPR. The cross-sectoral dominance of Danantara's authority creates opportunities for certain parties to exploit legal loopholes to commit acts that could lead to monopolistic practices and unfair business competition. Articles 25, 26, and 27 of Law No. 5 of 1999 and Article 86M of Law No. 1 of 2025 show that certain parties may abuse authority through the unfair centralization of cooperative affiliations in addressing the monopoly rights granted to Danantara, which may result the centralization of cooperative affiliations between BUMN and business partners become a crucial matter in building public trust for the realization of fair business competition.